A review of exploring collaboration and learning about climate change adaptation in BREEAM Communities - Naji, Sally; Julie Gwilliam (Technium: Romanian Journal of Applied Sciences and Technology, 2020)
This paper aims to establish a better understanding of the adaptation potential that can be provided through the use of Neighbourhood Sustainability Assessment tools, and how the adaptation effects and is affected by stakeholder collaboration and learning issues provided through the use of Neighbourhood Sustainability tools. An analytical framework will be developed which reviews of concepts and theories of system approach to adaptive management is presented. Characteristics of system approach and adaptive management are discussed across the stages of the development process, considering feedback from each stage. The framework will then be applied using BREEAM Communities tool, which illustrates that social adaptation indicators have been considered, but they need more enhancement in the long term. The paper concludes that the application of the framework that has been developed could enable evaluation of the influence of sustainability assessment tools at neighbourhood scale on organisation, participation, monitoring, risks assessment and responsibility issues towards the adaptation process at different stages of sustainable built environment.